Introduction to human disease : pathophysiology for the health professional - Loeffler, Agnes Gertrud, 1966-; Hart, Michael Noel, 1938- (Burlington, MA : Jones & Bartlett Learning, 2015)
Introduction to Human Disease: Pathophysiology for Health Professionals, Sixth Edition provides a broad overview of the most common and important human diseases for students pursuing careers in the health professions. Comprehensive yet accessible, it addresses the aspects of disease epidemiology, diagnosis, and treatment that are essential to clinical practice. The Sixth Edition of this popular text has been thoroughly updated to cover the latest advances in medical knowledge and practice, especially with regard to mental health and nutritional disorders. It also includes additional clinical information on treatments for diseases. Designed to facilitate learning, this essential reference features new full-color photos and illustrations, learning objectives, and practice questions for review and assessment. Introduction to Human Disease: Pathophysiology for Health Professions, Sixth Edition will help students gain a solid foundation in disease pathology and medical terminology to help them throughout their medical education.--Publisher.
Introduction to pathology -- Most frequent and significant diseases -- Diagnostic resources -- Injury, inflammation, and repair -- Hyperplasias and neoplasms -- Cancer -- Genetic and developmental diseases -- Vascular system -- Heart -- Hematopoietic system -- Bleeding and clotting disorders -- Lung -- Oral region, upper respiratory tract, and ear -- Gastrointestinal tract -- Liver, gallbladder, and pancreas -- Kidney, lower urinary tract, and male genital organs -- Female genital organs -- Breast -- Skin -- Eye -- Bones and joints -- Skeletal muscle and peripheral nerve -- Central nervous system -- Mental illness -- Endocrine system -- Infectious diseases -- Immunologic diseases -- Physical injury -- Chemical injury -- Nutritional disorders and alcoholism.
Author's names reversed on the fifth edition.
This book includes online access at www.jblearning.com, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Pathologic Processes -- physiopathology